Better together: Active and passive labor market policies in developed and developing economies - Clemente Pignatti; Eva Van Belle (IZA Journal of Development and Migration, 2021)
We investigate the macroeconomic impact of public expenditure in active labor market policies (ALMPs) and passive labor market policies (PLMPs) on main employment indicators (i.e., unemployment, employment, and labor force participation) for a large and novel panel database of 121 countries (36 developed, 64 emerging and 21 developing economies). Compared to previous studies, we include for the first time evidence from developing and emerging economies and explicitly examine the possible presence of complementarities between active and passive policies. We find that the interaction between interventions is crucial, as the effect of spending in either of the two policies is more favorable the more is spent on the other. Even the detrimental labor market effects of passive policies disappear on the condition that sufficient amounts are spent on active interventions. This complementarity seems even more important for emerging and developing economies.
Keywords: J08; E24; O1; 330; developing countries; evaluation; labor economics; public policy; welfare state